2003
DOI: 10.1055/s-2003-37654
|View full text |Cite
|
Sign up to set email alerts
|

An Expeditious Synthetic Access to β-(Z)-[(1-Propynyl)amino]enones and β-[(Z)-(1-Propynyl)amino]enoates

Abstract: An Expeditious Synthetic Access to b-(Z)-[(1-Propynyl)amino]enones and b-[(Z)-(1-Propynyl)amino]enoates A n E x p e d i t i o u s S y n t h e t i c A c c e s s t o β -( Z ) -[ ( 1 -P r o p y n y l ) a m i n o ] e n o n e s a n d E n o a t e s Abstract: The silver nitrate promoted reaction of propargyl bromide with (Z)-4-amino-3-penten-2-ones and (Z)-3-amino-2butenoates provides rapid access to β-(Z)-[(1-propynyl)amino]enones and β-[(Z)-(1-propynyl)amino]enoates respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Some of the methods described in the literature include the reaction of propargyl amines with α,β-acetylenic-or α,β-unsaturated ketones, 15,16 condensation of amines with 1,3-dicarbonyl compounds 17 gold-or CAN-catalyzed reaction, 18 Sonogashira cross-coupling of terminal alkynes with acyl chlorides 19 and N-alkylation of β-enaminones with 3-bromopropyne. 20 No reports have demonstrated the use of secondary amines, since they are less reactive than primary amines in the synthesis of N-propargylic β-enaminones, which are extremely important building blocks in organic synthesis. As a part of our program aiming at developing selective and safe methodologies for the preparation of new building blocks, herein we describe the synthesis of a series of N,N-arylpropargylic β-enamino trihalomethyl [ethoxy]ketones from the reaction between 4-alkoxy-1,1,1-trihalo[ethoxy]-3-alken-2-ones and propargyl amines.…”
Section: -6mentioning
confidence: 99%
“…Some of the methods described in the literature include the reaction of propargyl amines with α,β-acetylenic-or α,β-unsaturated ketones, 15,16 condensation of amines with 1,3-dicarbonyl compounds 17 gold-or CAN-catalyzed reaction, 18 Sonogashira cross-coupling of terminal alkynes with acyl chlorides 19 and N-alkylation of β-enaminones with 3-bromopropyne. 20 No reports have demonstrated the use of secondary amines, since they are less reactive than primary amines in the synthesis of N-propargylic β-enaminones, which are extremely important building blocks in organic synthesis. As a part of our program aiming at developing selective and safe methodologies for the preparation of new building blocks, herein we describe the synthesis of a series of N,N-arylpropargylic β-enamino trihalomethyl [ethoxy]ketones from the reaction between 4-alkoxy-1,1,1-trihalo[ethoxy]-3-alken-2-ones and propargyl amines.…”
Section: -6mentioning
confidence: 99%
“…2,3 It has been observed that functionalized pyrroles can be efficiently prepared using a two-step sequence, by propargylation of secondary enaminones using n-BuLi and propargyl bromide, followed by intramolecular hydroamination catalyzed by silver nitrate. 4 (C) Homolytic alkylation of heteroaromatic bases, i.e substituted histidine and histamine, is carried out with the help of silver nitrate, where silver-catalyzed oxidative decarboxylation of acids by peroxydisulfate takes place. The carboxylic acid acts as a source of alkyl radical, which leads to the formation of 2,3-disubstituted L-histidine methyl ester and a-N-trifluoroacetylhistamine.…”
Section: Introductionmentioning
confidence: 99%